Preparation of monodisperse silica powder from acid residue after extracting alumina from coal gangue. Issue 1 (10th November 2022) - Zhang, Tao; Yang, Huifen; Zhang, Hongbo; Zhang, Peng
Abstract: A new method for preparing monodisperse silica powder was introduced in this paper. Monodisperse silica powder was synthesized by sol–gel method using sodium silicate prepared from acid residue after alumina extraction from coal gangue leached by NaOH. The dissolution rate of SiO2 was determined according to the potassium fluosilicate volumetric method (GB/T 27974‐2011). The SiO2 dissolution rate reaching 92.74% when dissolution temperature calcined at 90°C for 90 min, the liquid–solid ratio was 8 ml/g, and the concentration of NaOH solution was 30%. The maximum specific surface area of silicon powder reaching 519m 2 /g when the concentration of sodium silicate was 0.6 mol/l, ethyl acetate concentration was 8%, anhydrous ethanol concentration was 5%, and the reaction time was 90 min. X‐ray fluorescence (XRF), X‐ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscope (SEM) showed that the content of SiO2 in the powder was 99.28%, the particle size was between 30 ~ 300 nm, and more than 90% of the particle size was below 100 nm.